2008
DOI: 10.1038/ja.2008.28
|View full text |Cite
|
Sign up to set email alerts
|

Diapolycopenedioic Acid Xylosyl Esters A, B, and C, Novel Antioxidative Glyco-C30-carotenoic Acids Produced by a New Marine Bacterium Rubritalea squalenifaciens

Abstract: Novel acyl glyco-carotenoic acids, diapolycopenedioic acid xylosyl esters A, B, and C, were isolated as red pigments by using chromatographic methods from a marine bacterium, Rubritalea squalenifaciens, belonging to subdivision 1 of Verrucomicrobia. The structures of these diapolycopenedioic acid xylosyl esters were determined to be 4-[2-O-acyl-b -D-xylopyranosyl] hydrogen 4,4Ј-diapo-Y ,Y -carotene-4,4Ј-dioate by spectroscopic analysis. Diapolycopenedioic acid xylosyl ester A showed potent antioxidative activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…[7][8][9] These studies have reported the isolation of rare carotenoids, (3R)-saproxanthin and myxol, from Flavobacteriaceae, 7 and novel glyco-C 30 carotenoids (diapolycopenedioic acid xylosyl esters A, B, and C from Rubritalea squalenifaciens 8 and methyl glucosyl-3,4-dehydroapo-8¢-lycopenoate from Planococcus maritimus 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] These studies have reported the isolation of rare carotenoids, (3R)-saproxanthin and myxol, from Flavobacteriaceae, 7 and novel glyco-C 30 carotenoids (diapolycopenedioic acid xylosyl esters A, B, and C from Rubritalea squalenifaciens 8 and methyl glucosyl-3,4-dehydroapo-8¢-lycopenoate from Planococcus maritimus 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have performed the analysis of novel or rare types of carotenoids from new colored marine bacteria, which were classified to belong to a new species by the 16S rRNA analyses [7,8]. These studies have reported the isolation of rare carotenoids, (3R)-saproxanthin and myxol, from Flavobacteriaceae [7], and novel carotenoids glyco-C 30 -carotenoic acids (diapolycopenedioic acid xylosyl esters A, B, and C) from Rubritalea squalenifaciens [8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have reported the isolation of rare carotenoids, (3R)-saproxanthin and myxol, from Flavobacteriaceae [7], and novel carotenoids glyco-C 30 -carotenoic acids (diapolycopenedioic acid xylosyl esters A, B, and C) from Rubritalea squalenifaciens [8]. This time, we have found a novel carotenoioic acid ester produced by a marine bacterium Planococcus maritimus, and describe its structural determination (including the absolute configurations) as methyl glucosyl-3,4-dehydroapo-8'-lycopenoate, its antioxidative activity included.…”
Section: Introductionmentioning
confidence: 99%
“…), Rubritella squalenifaciens (Shindo et al . ,, ), Planococcus maritimus (Shindo et al . ) and Halobacillus halophilus (Köcher et al .…”
Section: Introductionmentioning
confidence: 99%